Disruption of IL-17-mediated immunosurveillance in the respiratory mucosa results in invasive Streptococcus pyogenes infection - Jamie-Lee Mills; Ailin Lepletier; Victoria Ozberk; Jessica Dooley; Jacqualine Kaden; Ainslie Calcutt; Yongbao Huo; Allan Hicks; Ali Zaid; Michael F. Good; Manisha Pandey (Frontiers in Immunology, 2024)
IntroductionStreptococcus pyogenes is a Gram-positive pathogen that causes a significant global burden of skin pyoderma and pharyngitis. In some cases, infection can lead to severe invasive streptococcal diseases. Previous studies have shown that IL-17 deficiency in mice (IL-17−/−) can reduce S. pyogenes clearance from the mucosal surfaces. However, the effect of IL-17 on the development of severe invasive streptococcal disease has not yet been assessed.MethodsHere, we modeled single or repeated non-lethal intranasal (IN) S. pyogenes M1 strain infections in immunocompetent and IL-17−/− mice to assess bacterial colonization following a final IN or skin challenge.ResultsImmunocompetent mice that received a single S. pyogenes infection showed long-lasting immunity to subsequent IN infection, and no bacteria were detected in the lymph nodes or spleens. However, in the absence of IL-17, a single IN infection resulted in dissemination of S. pyogenes to the lymphoid organs, which was accentuated by repeated IN infections. In contrast to what was observed in the respiratory mucosa, skin immunity did not correlate with the systemic levels of IL-17. Instead, it was found to be associated with the activation of germinal center responses and accumulation of neutrophils in the spleen.DiscussionOur results demonstrated that IL-17 plays a critical role in preventing invasive disease following S. pyogenes infection of the respiratory tract.